2021
DOI: 10.1021/acscatal.1c02795
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved XAS Provides Direct Evidence for Oxygen Activation on Cationic Iron in a Bimetallic Pt-FeOx/Al2O3 Catalyst

Abstract: Reducible oxides are effective aerobic oxidation catalysts being able to activate molecular oxygen. This ability is generally attributed to the high concentration of oxygen vacancies serving as oxygen activation sites. At the same time, the mechanism of oxygen activation remains unclear since surface oxygen activation sites cannot be easily detected using conventional methods. In this work, we unraveled the mechanism of oxygen activation over iron sites of Pt-FeO x /Al 2 O 3 during carbon monoxide oxidation us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 56 publications
2
37
0
Order By: Relevance
“…35,37,38 There was little difference in band position and relative intensity between Pt-Na/Al-5h and Pt-Na/Al-2h, demonstrating that the valence state of Pt species in both samples was similar. 39 This result also implied that the Pt species with different particle sizes could be reduced to species with similar valence states under the hydrogen reduction condition of 300 °C.…”
Section: Characterization Of Pt Speciesmentioning
confidence: 84%
“…35,37,38 There was little difference in band position and relative intensity between Pt-Na/Al-5h and Pt-Na/Al-2h, demonstrating that the valence state of Pt species in both samples was similar. 39 This result also implied that the Pt species with different particle sizes could be reduced to species with similar valence states under the hydrogen reduction condition of 300 °C.…”
Section: Characterization Of Pt Speciesmentioning
confidence: 84%
“…The first Fe-O shell of FeOOH is at ~1.98 Å, attributing to a coordination number (N) of 5.8 (Sadykov et al, 2021), which indicates many oxygen vacancies in the matrix of crystal. As for Pt/FeOOH, the first Fe-O shell peak appears at ~1.94 Å, corresponding to a coordination number (N) of 6.0 (Table 3) (Sadykov et al, 2021), which is nearly the theoretical value of an octahedral structure. These results verified the good crystalline nature of Pt/FeOOH and the Pt-O-Fe interfaces.…”
Section: Structure Evolution Of Feooh Qds Induced By the Metal-suppor...mentioning
confidence: 99%
“…Moreover, the shortened Fe-O bond and elongated Fe-Fe bond in Pt/FeOOH compared with those of FeOOH consolidate the Pt-O-Fe-rich interfaces. We tried to probe the local coordination chemistry of Pt atoms; unfortunately, the XAS (Liu et al, 2018;Ren et al, 2019;Sadykov et al, 2021).…”
Section: Structure Evolution Of Feooh Qds Induced By the Metal-suppor...mentioning
confidence: 99%
“…In our previous work, we demonstrated that operando quick XAS combined with a transient experimental strategy provides quantitative information on the redox activity of metal centers involved in the Mars-van Krevelen mechanism of carbon monoxide and ethanol oxidation on various catalysts. [28][29][30][31][32] In particular, for the bilayered VOx/TiOx/SiO2 catalyst, we have shown that V 5+ to V 4+ reduction upon ethanol oxidation is kinetically coupled with acetaldehyde formation, while the redox activity of titanium was shown to be not directly involved in the catalytic cycle. [32] In this work, we applied the same transient XAS methodology to uncover the redox processes involved in ethanol ODH over VOx/CeO2 catalysts.…”
Section: Introductionmentioning
confidence: 99%